2006
DOI: 10.1007/bf02971247
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of left ventricular ejection fraction induced by dipyridamole on Tl-201 gated myocardial perfusion imaging predicts significant coronary artery disease

Abstract: Dipyridamole-induced worsening of LVEF, as shown by Tl-201 gated SPECT, is a valuable nonperfusion marker of significant CAD. Although the sensitivity of LVEF worsening in detecting significant CAD is only 35%, the specificity is as high as 93%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
1
17
3
Order By: Relevance
“…Johnson et al [4] reported worsening of the LVEF after adenosine in 22 of 61 patients (36%) with reversible perfusion defects; 16 of them underwent treadmill exercise and only 6 had dipyridamole stress. However, recent studies show that nearly 33% of patients with normal myocardial perfusion imaging results after undergoing dipyridamole or adenosine stress test had a worsening of the LVEF, indicating that vasodilator stress can also lead to myocardial stunning [9,19]. Lee et al [20] investigated poststress LV dysfunction in patients undergoing dipyridamole stress imaging, and found worsening of the LVEF in 8 (42%) of 19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al [4] reported worsening of the LVEF after adenosine in 22 of 61 patients (36%) with reversible perfusion defects; 16 of them underwent treadmill exercise and only 6 had dipyridamole stress. However, recent studies show that nearly 33% of patients with normal myocardial perfusion imaging results after undergoing dipyridamole or adenosine stress test had a worsening of the LVEF, indicating that vasodilator stress can also lead to myocardial stunning [9,19]. Lee et al [20] investigated poststress LV dysfunction in patients undergoing dipyridamole stress imaging, and found worsening of the LVEF in 8 (42%) of 19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with CAD, the narrowed coronary arteries cannot respond to rapid changes in blood flow induced by adenosine, and the adenosine cascade induces myocardial stunning and results in worsening of the LVEF [22]. For detecting significant CAD, the sensitivity of the reversible regional WM abnormality is significantly higher than that of LVEF worsening (70 vs. 35%, respectively) [19]. However, the specificity of LVEF worsening was significantly higher than that of reversible regional WM abnormality (93 vs. 73%, respectively) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in EDV (3 ± 6 ml vs. −1 ± 5 ml; P = 0.01) and the stress-to-rest ratio of EDV (1.04 ± 0.09 vs. 0.99 ± 0.08; P < 0.02) after stress were greater in ATP than in Ex group (Table 2). In addition, changes in ESV (3 ± 5 ml vs. 1 ± 5 ml; P = 0.08) and the stress-to-rest ratio of ESV (1.15 ± 0.26 vs. 1.05 ± 0.21; P = 0.07) after stress were also greater in ATP than in Ex group with the difference being of borderline signifi cance ( ESV increase or EF decrease, emerged as an important marker for severe and extensive CAD [6][7][8][9][10][11][12][13]15], the results of this study, evaluating cases with normal scintigraphic fi ndings, should be kept in mind when interpreting post-ischemic stunning. Small but signifi cant increases were observed in EDV and ESV only following ATP stress (Figs.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Furthermore, post-ischemic myocardial stunning as assessed by gated SPECT, and which is regarded as one of the key mechanisms of transient ischemic LV dilation, has emerged recently as an important marker of severe and extensive coronary artery disease (CAD) [6][7][8][9][10][11][12][13][14][15][16][17][18]. Earlier studies, however, applied various protocols involving a wide range of intervals between the end of stress and the start of data acquisition from 10 min to 60 min, and different radiotracers such as 99m Tc sestamibi, 201 Tl, or dual isotopes, and employed different stress methods either with exercise or with pharmacologic loading [6][7][8][9][11][12][13][14][15][16][17][18]. The occurrence of post-ischemic stunning was also reported to show a wide range from 13% to 46% [6,8,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological stimulation differs from exercise stress in that it does not cause demand ischemia. The number of studies that have compared exercise and pharmacological stress effects on TLVD are limited in number and confl icting [2,[11][12][13][14][15]. Therefore, the objective of this study was to determine whether TLVD could also be seen after pharmacological stress (dipyridamole).…”
Section: Introductionmentioning
confidence: 98%